A Biodegradable, Sustained-Released, Tacrolimus Microfilm Drug Delivery System for the Management of Allergic Conjunctivitis in a Mouse Model - Liu, Yu-Chi (2018)
Purpose: To investigate the drug release profiles of a tacrolimus-loaded poly(D,L-lactide-co-ε-caprolactone) (PLC) microfilm, and to evaluate its efficacy on the treatment of allergic conjunctivitis using a mouse model.